2021
DOI: 10.30827/profesorado.v25i1.8302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del desempeño docente: Una mirada desde las agencias certificadoras

Abstract: El profesorado ejerce una alta influencia sobre los estudiantes, que hace indispensable una preparación continua y, por ende, una evaluación formativa del desempeño docente. La aportación tiene como objetivo el determinar las debilidades y fortalezas del modelo de evaluación del profesorado universitario desde la perspectiva de las entidades certificadoras. Se aplicaron cinco entrevistas en profundidad a responsables del profesorado de la ANECA y agencias autonómicas y se realizó un análisis documental de 17 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
4
0
5
Order By: Relevance
“…The results showed that both kinds of training are the variables that most predicted the proper functioning of the methodological principles, the teachers’ functions and the resources needed to adapt to special educational needs in competency-based learning. Goldman and Grimbeek (2015), Méndez-Alonso et al (2015) and Ramírez (2016) also stressed that the implementation of the key competences requires specific teacher training on the teaching models that best fit competency-based learning and the needs of the educational context. Furthermore, in this study it was discovered that the proper application of the methodological principles, the proper performance of teachers’ functions and the appropriate curricular adaptations predict the attainment of the objectives and the evaluation of the curricular contents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that both kinds of training are the variables that most predicted the proper functioning of the methodological principles, the teachers’ functions and the resources needed to adapt to special educational needs in competency-based learning. Goldman and Grimbeek (2015), Méndez-Alonso et al (2015) and Ramírez (2016) also stressed that the implementation of the key competences requires specific teacher training on the teaching models that best fit competency-based learning and the needs of the educational context. Furthermore, in this study it was discovered that the proper application of the methodological principles, the proper performance of teachers’ functions and the appropriate curricular adaptations predict the attainment of the objectives and the evaluation of the curricular contents.…”
Section: Discussionmentioning
confidence: 99%
“…Este enfoque de aprendizaje demanda que el docente adquiera un nuevo rol que, a su vez, le requiere formación específica (e.g., Álvarez-Castrillón, Rodríguez-Martín, & Álvarez-Arregui, 2014; Capraro, Capraro, & Helfeldt, 2010; De-Juanas, Martín, & Pesquero, 2016; Lleixà, Capllonch, & González, 2015; Méndez-Alonso, Méndez-Giménez, & Fernández-Río, 2015; Méndez-Giménez, Sierra-Arizmendiarrieta, & Mañana-Rodríguez, 2013; Ramírez, 2016; Villa, Campo, Arranz, Villa, & García, 2013). La resistencia de los docentes, la falta de formación, la carencia de trabajos interdisciplinares entre los maestros, y el contexto sociopolítico han sido señaladas como importantes limitaciones (Méndez-Giménez et al, 2013), lo que provoca que el pretendido cambio de la administración no genere los efectos deseados (Monarca & Rappoport, 2013).…”
Section: Modelo De Predicción Para La Inclusión De Las Competencias E...unclassified
See 2 more Smart Citations
“…En el caso particular de España, la Agencia Nacional de evaluación de la Calidad y Acreditación (ANECA) tiene la función de evaluar las actividades de los docentes desde una perspectiva de gestión que se ha constituido en un requisito previo para la contratación de investigadores y profesores universitarios. Este proceso de acreditación (evaluación externa del currículo se entiende como un asunto necesario en términos de legitimación; sin embargo, es preciso hacer una revisión de este, para alcanzar espacios de actividad docente democráticos, que no lleven al sistema a una especie de perversión de los fines de la calidad como instrumento de mejoramiento, pues ha sido criticado especialmente por propiciar miradas mercantiles sobre la profesión docente, centradas casi de manera exclusiva en la producción académica (Aravena & Gairín, 2021;Díez-Gutiérrez, 2020;2021).…”
Section: Introductionunclassified